How to Avoid Medico-Legal Litigations in Performing High Intensity Focused Ultrasound Ablation for Treating Fibroids and Adenomyosis - Felix Wong; Peng Hao Wong; Thomas Kwok To Li (IMR Press, 2023)
High-intensity focused ultrasound (HIFU) ablation is the latest advance in surgery. It is an accepted treatment for uterine fibroids and adenomyosis in Asia. Even though it is a non-invasive surgery, with preliminary results of a very low complication rate, adverse events and complications occur. In modern medicine, patients are likely to file claims should a complication or injury occur and treatment results fall short of expectations. The increasing trend of litigations in Obstetrics and Gynaecology undoubtedly generates anxiety among gynaecologists operating with this new surgical technique. This paper is written to guide doctors performing this new HIFU treatment to reduce and steer clear of potential medico-legal problems.